(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Oratory is not merely the act of public speaking; it is a fundamental communicative practice that has evolved as a mirror to human civilization. It represents the intersection of linguistic precision, psychological persuasion, and social governance.